Group selection for processes with multiple quality characteristics. Issue 16 (18th August 2018) - Lin, Chen-Ju; Pearn, W. L.; Huang, J. Y.; Chen, Y. H.
ABSTRACT: Evaluating and comparing process capabilities are important tasks of production management. Manufacturers should apply the process with the highest capability among competing processes. A process group selection method is developed to solve the process selection problem based on overall yields. The goal is to select the processes with the highest overall yield among I processes under multiple quality characteristics, I > 2. The proposed method uses Bonferroni adjustment to control the overall error rate of comparing multiple processes. The critical values and the required sample sizes for designated powers are provided for practical use.